The Proliferation of Glioblastoma Is Contributed to Kinesin Family Member 18A and Medical Data Analysis of GBM - Wang, Lei-Bo; Zhang, Xue-Bin; Liu, Jun; Liu, Qing-Jun (Frontiers in Genetics, 2022)
Background Glioblastoma (GBM) is widely known as a classical kind of malignant tumor originated in brain. And the mobidity and mortality of it are both high. Targeted therapy has shown great promise in the treatment of glioblastoma, but more promising targets, including effective therapeutic targets, remain to be identified. 18A (KIF18A) is a microtubule-based motor protein that is dysregulated and involved in the progression of multiple human cancers. However, the possible effects of KIF18A on GBM progression is still unclear. Methods We performed DEG analysis, Medical Data analysis and Network analysis to identify critical genes affecting giloma progression. We also performed immunohistochemical analysis of KIF18A levels in 94 patients with glioblastoma and associated surrounding tissues. Patients were divided into two groups according to high and low expression. A clinical analysis We then analyzed the potential associations between KIF18A expression and clinical characteristics of 94 GBM patients. We then investigated the effects of KIF18A on GBM cell proliferation by colony establishment, mtt and immune blogging. The possible effect of KIF18A on GBM tumor growth was determined in mice. Results We identified KIF18A as a potential gene affecting GBM progression. We further demonstrated that GBM tissues expressed KIF18A much higher. Its presentation was associated with recurrence in glioblastoma patients. We believe KIF18A promotes gbm cell proliferation. Conclusion We demonstrated that KIF18A could be used to the treatment of GBM as a promising target.